Inventory of Potentially Allelopathic Plants in Laut Dendang Village and Their Effects on Mustard Greens (Bransica juncea l.) - indayana Febriani Tanjung; Ayu Sahara Tumanggor; M Rizki; Nada Thahira; Febry Ramadhani (Jurnal Biologi Tropis, 2023)
Allelopathy comes from the Greek words allelon, which means "one another", and pathos, which means "to suffer". This research was conducted in October 2022 in the village of Lau Dendang, Percut Sei Tuan District. The method used is a combined method where direct surveys are carried out first, observations are made using the plot method and later experiments are carried out on other plants. In an inventory of allelopathic plants in Laut Dendang Village, there are several different species, namely Ageratum conyzoides L, Mimosa pudica, Rumohra adiantiformis, Pyrrosia eleagnifolia, Blumea balsamifera, Cyperus haspan, Ludwigia peruviana (L.) H. Hara and Imperata Cyperus rotundus. The most common of Cyperaceae.